Relationship between Economic Growth, Renewable Energy, International Trade and Sukuk: A Case Study of 12 Sukuk User Countries - Aisah, Anik Nur; Bawono, Anton (Universitas Muhammadiyah Prof. DR HAMKA., 2023)
The purpose of this study is to examine the simultaneous influence of Renewable Energy, International Trade, and Sukuk on Economic Growth in 12 Sukuk-consuming countries for the 2014-2021 period. This type of research is Quantitative research using the Simultaneous Two-Stage Least Squares method. Based on the results of the study, it was obtained that Renewable Energy does not affect Economic Growth, it was also found that exports affect renewable energy, but not with Sukuk. So these variables cannot simultaneously encourage renewable energy to affect economic growth. For international trade (exports and imports) it affects economic growth. This study also found that Sukuk does not affect economic growth, in this study Sukuk is still influenced by exports. However, the existing influence has not been able to affect economic growth, since exports have a positively insignificant effect on Sukuk.